PENGEMBANGAN LEMBAR KERJA PRAKTIKUM MATA PELAJARAN INSTALASI MOTOR LISTRIK KELAS XI TEKNIK INSTALASI TENAGA LISTRIK DI SMK NEGERI 1 LUBUK PAKAM - Nasution, Erwin Yusuf; Amin, Muhammad (JEVTE Journal of Electrical Vocational Teacher Education, 2023)
Abstract This research aims to: 1). To develop a practical worksheet for the electric motor installation subject class XI TITL at SMKN 1 Lubuk Pakam, 2). To test the feasibility of the practical worksheet for the electric motor installation subject that has been created for class Lubuk Pakam. This research methodology is research and development (Research & Development) with the Four-D Models development model. Four-D Models consists of 4 stages, namely: 1). Definition (Define), 2). Design, 3). Development (Develop), 4). Dissemination (Dissaminate). The Dissaminate stage was not carried out due to the narrow scope of the research. The instrument used is a non-test instrument in the form of a questionnaire with a Likert scale of 5 answer choices. The questionnaire was validated by an evaluation expert. Based on the results of the analysis and discussion, it is known that: 1) This development research produces learning resources in accordance with the syllabus, namely a practical worksheet consisting of 11 practical activities. 2) The level of suitability of the practicum worksheet is known from the assessment results of material experts, media experts, and the results of teacher and student responses. The results of material expert validation which included aspects of appropriateness of content, language, presentation and benefits achieved an average score of 116 with a percentage of 92.8% in the "very appropriate" category. Media expert validation results covering aspects of appearance, ease of use, consistency, format and graphics achieved an average score of 99.4 with a percentage of 90.36% in the "very feasible" category. Based on teacher responses, they obtained an average score of 117.33 with a percentage of 93.86%. Meanwhile, student responses obtained an average score of 102.68 with a percentage of 85.56% in the "very appropriate" category. Key Words: Practical Worksheet, Electric Motor Installation.. AbstrakPenelitian ini bertujuan untuk: 1).Untuk mengembangkan Lembar kerja praktikum mata pelajaran instalasi motor listrik kelas XI TITL di SMKN 1 Lubuk Pakam, 2).Untuk menguji kelayakan lembar kerja praktikum mata pelajaran instalasi motor listrik yang telah dibuat untuk kelas XI di SMKN 1 Lubuk Pakam. Metodologi penelitian ini adalah penelitian dan pengembangan (Research & Development) dengan model pengembangan Four-D Models. Four-D Models terdiri dari 4 tahap, yaitu: 1). Pendefinisian (Define), 2). Perancangan (Design), 3). Pengembangan (Develop), 4). Penyebaran (Dissaminate). Tahap Dissaminate tidak dilaksanakan karena lingkup peneltian yang sempit. Instrumen yang digunakan adalah instrumen non tes berupa angket dengan skala Likert 5 pilihan jawaban. Angket divalidasi oleh seorang ahli evaluasi. Berdasarkan hasil analisis dan pembahasan, diketahui bahwa: 1) Penelitian pengembangan ini menghasilkan sumber belajar sesuai dengan silabus yaitu lembar kerja praktikum yang terdiri dari 11 kegiatan praktik. 2) Tingkat kelayakan lembar kerja praktikum diketahui dari hasil penilaian ahli materi, ahli media, dan hasil respon guru dan siswa. Hasil validasi ahli materi yang meliputi aspek kelayakan isi, kebahasaan, sajian, dan manfaat mencapai rata-rata skor 116 dengan presentase 92.8% pada kategori œsangat layak. Hasil validasi ahli media yang meliputi aspek tampilan, kemudahan penggunaan, konsistensi, format, dan kegrafikan mencapai rata-rata skor 99.4 dengan presentase 90.36% pada kategori œsangat layak. Berdasarkan respon guru memperoleh skor rata-rata 117.33 dengan presentase 93.86%. Sementara itu untuk respon siswa memperoleh skor rata-rata 102.68 dengan presentase 85.56% pada kategori œsangat layak. Kata kunci : Lembar Kerja Praktikum, Instalasi Motor Listrik.